Kebijakan Pembangunan Desa Tertinggal Berbasis Indeks Desa Membangun (IDM) dan Potensi Lokal - Suroso - Suroso (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2020)
ENGLISHUnder-developed villages are challenges for local government development so the under-developed villages become developing ones . The objectives of this study are (1) to identify the existence of under-developed villages in term of IDM and local potential; and (2) to analyze the development needs for under- developed villages based on IDM and local potential in the study area. This study used a descriptive-quantitative approach. This study was conducted in Pati Regency. The research used primary and secondary data. The secondary data were collected by observing related documents. The primary data were obtained through interviews with competent informants. The study used descriptive analysis. The results showed that in Pati Regency there are 15 under- developed villages spread out in 7 districts which have different characterictics in term of IKS, IKE and IKL. The under-developed villages based on IDM mainly need economic development (IKE) and environmental one (IKL). In order to get better achievement, the development for the under-developed villages become developing or developed villages, it should be based on local potentials of the villages. Moreover the development for the under-developed villages become developing or developed villages, it can be realized soon if there are supports from stakeholders including related agencies. INDONESIADesa tertinggal merupakan tantangan pembangunan daerah sehingga desa tersebut bisa menjadi desa berkembang. Tujuan penelitian ini adalah (1) mengidentifikasi eksistensi desa tertinggal dari perspektif IDM dan potensi lokal; dan (2) menganalisis kebutuhan pembangunan desa tertinggal berbasis pada IDM dan potensi lokal di area studi. Penelitian menggunakan pendekatan deskriptif-kuantitatif. Penelitian ini dilakukan di Kabupaten Pati. Penelitian menggunakan data primer dan data sekunder. Pengumpulan data sekunder dilakukan dengan observasi dokumen terkait. Pengumpulan data primer dilakukan dengan wawancara dengan informan yang kompeten. Teknik analisis data menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa di Kabupaten Pati desa tertinggal sebanyak 15 desa yang tersebar di 7 kecamatan, dengan karakteristik IDM yang bervariasi pada IKS, IKE dan IKL. Pembangunan desa tertinggal berdasarkan IDM lebih membutuhkan pembangunan ekonomi (IKE) dan pembangunan lingkungan (IKL). Guna memperoleh hasil yang lebih baik, pembangunan desa tertinggal menuju desa berkembang dan desa maju perlu memperhatikan potensi lokal desa. Selain itu pembangunan desa tertinggal menuju desa berkembang atau maju bisa segera terwujud bila ada dukungan stakeholder termasuk dinas terkait.